Heroic workers and angry young men: Nostalgic stories of class in England. (December 2014) - Lawler, Stephanie
This article discusses nostalgic images of white working-class life through the twin figures of 'the heroic worker' and 'the angry young man'. Using a case study of a discussion of Roy Williams' play Vultures, I consider the ways in which nostalgic figures are used to position a contemporary white working class as lacking value. I argue that these nostalgic figures provide anchor points in decline narratives which, I argue, have come to define the ways in which the English white working class are represented. Hence, I argue that some forms of nostalgic class representations may be one means through which continued disparagement of contemporary white working-class people is rendered respectable.